Nutrition Beyond the Health Sector : A Profile of World Bank Lending in Nutrition from 2000 to 2006 - Garrett, James; El Hag El Tahir, Safinaz (World Bank, Washington, DC, 2013)
The World Bank report Repositioning Nutrition as Central to Development (2006) explicitly recommended improving nutrition by not only working through the health sector, but also in non-health sectors such as agriculture and education. This report provides descriptive and financial profiles of the Bank's recent portfolio in nutrition (from FY2000 to late FY2006) to note the extent to which the Bank has actually gone outside the health sector to work on nutrition. In this period, 41 projects were assigned a theme of "food and nutrition security." Just over half of them (22 out of 41) had nutrition-related components or activities. Of these 22 projects, half fell within the health sector, and half fell outside.